Concept analysis of collaboration in implementing problem-based learning in nursing education - Mahlasela A. Rakhudu; Mashudu Davhana-Maselesele; Ushanatefe Useh (AOSIS, 2016)
Objectives: The purpose of this concept analysis was to better understand and define collaboration as it relates to the implementation of problem-based learning (PBL). Methods: The process of concept analysis was conducted in three phases; namely, theoretical or literature review, empirical or fieldwork; and analysis phases. Rodgers' evolutionary approach was used to clarify the attributes, antecedents, surrogate, related terms and consequences of collaboration in implementing PBL. The search key terms were 'collaboration', 'problem-based learning', 'nursing' and 'nursing education'. The search was performed in the Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medline and PsycINFO databases. The articles were reviewed for trends that would reflect the current knowledge for collaboration as a concept. Descriptive qualitative study was used to collect data purposively from participants of three universities offering PBL in Republic of South Africa and three hospitals where PBL students are placed. Results: Collaboration in implementing PBL is described as using the following terms: interpersonal, interactive and personal process, shared goal and governance. The antecedents of collaboration include commitment and support; common goal; formal agreement; training and development; and monitoring and evaluation of tools and mechanisms. Consequences of collaboration in implementing PBL are as follows: information, resource and expertise sharing; personal development and mentoring; creation of supportive and nurturing environment; professional socialisation; improved students' outcomes; and effective utilisation of resources. Conclusion: Effective collaboration within nursing education and with other healthcare professionals to achieve quality outcomes in an increasingly interdependent higher education system continues to grow in importance.